2017
DOI: 10.1002/jso.24740
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for recurrence of locally advanced differentiated thyroid cancer

Abstract: Recurrent laryngeal nerve (n = 31) and trachea (n = 30) were most commonly invaded organs by tumor. At the mean follow-up of 81.7 months, LRR occurred in 15 patients and/or DM was detected in 15 patients (10 developed LRR and DM). By multivariate analysis, R1 resection (positive margin) and pN1b stage increased risk of LRR with a fold of 3.16 [95%CI 1.08-9.24, P = 0.03] and 5.92 [1.61-21.7, P = 0.007], respectively. Also, they increased risk of total recurrence with a fold of 3.04 [95%CI 1.26-7.31, P = 0.01] a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…In the 8th edition of the tumour-node-metastasis classification, the microscopic ETE was no longer considered as criterion for the definition of T3 disease, while gross extrathyroidal extension as an unfavourable prognostic factor was underlined [25]. Gross ETE which develops from microscopic ETE can result in local invasion to important organs or tissues such as the trachea, RLN, oesophagus, or even the carotid artery, which further complicates surgery and worsens the prognosis of thyroid cancer [26]. Thus, individualised treatment plans should be determined based not only on the biological characteristics of PTMC, but also on its location in the thyroid lobe.…”
Section: Discussionmentioning
confidence: 99%
“…In the 8th edition of the tumour-node-metastasis classification, the microscopic ETE was no longer considered as criterion for the definition of T3 disease, while gross extrathyroidal extension as an unfavourable prognostic factor was underlined [25]. Gross ETE which develops from microscopic ETE can result in local invasion to important organs or tissues such as the trachea, RLN, oesophagus, or even the carotid artery, which further complicates surgery and worsens the prognosis of thyroid cancer [26]. Thus, individualised treatment plans should be determined based not only on the biological characteristics of PTMC, but also on its location in the thyroid lobe.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective analysis by Kim et al found 29.4% of patients with classical type PTC between 1-4 cm had contralateral cancers at the time of surgery. Importantly, patients who underwent only hemithyroidectomy were excluded from the study, and the authors do not state how many, if any, of these patients would have been eligible for hemithyroidectomy under the ATA guidelines (78). Notably, many of the features denoted as high risk by the ATA are strongly associated with multifocality (77,(79)(80)(81); suggesting that these patients would have undergone total thyroidectomy under the current guidelines.…”
Section: Extent Of Surgery For Differentiated Tumorsmentioning
confidence: 99%
“…2 Surgical resection is the primary management SCC of the aerodigestive tract, potentially with concurrent chemo-radiation therapy depending on the extent of the disease. 3 A modern advance in robotic oncologic surgical techniques of the head and neck, trans-oral robotic surgery (TORS), has been developed using the da Vinci robotic system (Intuitive Surgical, Sunnyvale, CA) and demonstrated use in resection of orophangyeal and laryngeal SCC with promising results on functional preservation. 4 The da Vinci system relies on conventional optical imaging using a high resolution monitor, but studies have aimed to expand the optical imaging capabilities utilized.…”
Section: Introductionmentioning
confidence: 99%